Resolving X-ray photoelectron spectra of ionic liquids with difference spectroscopy. Issue 1 (6th December 2018) - Clarke, Coby J.; Maxwell-Hogg, Steven; Smith, Emily F.; Hawker, Rebecca R.; Harper, Jason B.; Licence, Peter
Abstract : Difference spectroscopy of functionalised ionic liquids can help resolve photoemission signals beyond that previously thought possible. Abstract : X-ray photoelectron spectroscopy (XPS) is a powerful element-specific technique to determine the composition and chemical state of all elements in an involatile sample. However, for elements such as carbon, the wide variety of chemical states produce complex spectra that are difficult to interpret, consequently concealing important information due to the uncertainty in signal identity. Here we report a process whereby chemical modification of carbon structures with electron withdrawing groups can reveal this information, providing accurate, highly refined fitting models far more complex than previously possible. This method is demonstrated with functionalised ionic liquids bearing chlorine or trifluoromethane groups that shift electron density from targeted locations. By comparing the C 1s spectra of non-functional ionic liquids to their functional analogues, a series of difference spectra can be produced to identify exact binding energies of carbon photoemissions, which can be used to improve the C 1s peak fitting of both samples. Importantly, ionic liquids possess ideal chemical and physical properties, which enhance this methodology to enable significant progress in XPS peak fitting and data interpretation.